أثر تطبيق معايير الحكم الرشيد على الإصلاح الإداري في دولة الإمارات العربية المتحدة (The impact of the application of good governance standards on administrative reform in the UAE ) - الميسري, إحسان عبدالله محمد الهارش; عبدالسلام, الفاتح عبدالله (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
تعالج هذه الدراسة أثر تطبيق معايير الحكم الرشيد على الإصلاح الإداري في دولة الإمارات العربية المتحدة، وكيف ساهم التوجه الحكومي للدولة في تطبيق الحكم الرشيد وتحقيق قدر لا بأس به من مؤشرات نوعية في الادارة العامة والقطاع العام ورضا المواطنين ومكافحة الفساد الذي يعد من أهم الاسباب التي تعيق التنمية وتهدر موارد الدولة، ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي التحليلي. وقد توصلت الدراسة إلى مجموعة من النتائج أهمها: أن هناك تقدماً نسبياً حققته دولة الإمارات في هذا المجال لاسيما في مجال مكافحة الفساد وتحقيق مراتب عالمية متقدمة بالإضافة إلى تطور الأداء الحكومي بقدر كبير، الا أن عدداً من التحديات يتطلب المزيد من الاجراءات لتحقيق الشفافية وتفعيل المساءلة. الكلمات المفتاحيّة: الحكم الرشيد، الإصلاح الإداري، رؤية الإمارات 2021، مكافحة الفساد. Abstract This study addresses the impact of the application of good governance standards on administrative reform in the UAE, and how the government's approach to the implementation of good governance contributed to achieving a good number of qualitative indicators in public administration, public sector, citizen satisfaction and combating corruption, which is one of the main reasons Which has hindered development and wasted resources of the state. The study reached a number of results, the most important of which is that there is a relative progress achieved by the UAE in this field, especially in the field of combating corruption and achieving advanced international rankings in addition to the development of government performance. Requires further measures to achieve transparency and accountability. Keywords: Good Governance, Administration reform, UEA Vision 2021, Anti-corruption.